A tale of two turnarounds at EDS : the Jordan rules - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
The case briefly describes the history of Electronic Data Systems (EDS) under Ross Perot and GM before turning to the beginning of a tumultuous decade in the late 1990s.